Test Case Analysis with Keyword-Driven Testing Approach on Angkasa Website Using Katalon Studio Tools - Reynaldi Prama Octavially; Rosa Reska Riskiana; Kusuma Ayu Laksitowening; Dana Sulistyo Kusumo; Monterico Adrian; Nungki Selviandro (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2021)
Abstract— Testing a software is an important stage of a series of software development. Functional testing of each feature on the Angkasa website is intended to try out the function to match the required specifications. To achieve a functional test result, there are elements of features on the web page that require keywords. These keywords are used to perform actions or actions in running a web page, these keywords will help in making Test Cases for the testing process. Because it takes the right keywords to test on the web. To overcome this problem, this study analyzes the use of the Keyword Driven Testing approach for making Test Cases through the Katalon Studio tools. Keyword Driven Testing is one of the concepts in ISO/IEC/IEEE 29119, namely Keyword Driven Testing in The Test Design Process. The results of the analysis show that making Test Cases with Keyword Driven testing is easier to understand and is fully supported by the Katalon Studio tools. However, when creating test cases, not all keywords can be added automatically, so they need to be added manually.